Integrated Imaging of Avascular Serous Pigment Epithelium Detachment in Age-related Macular Degeneration. Issue 1 (2017) - Querques, Giuseppe; Pastore, Marco R.; Khlifi, Houda; Georges, Anouk; Querques, Lea; Souied, Eric H.
Introduction: This study describes the imaging of avascular serous pigment epithelial detachment (PED) in age-related macular degeneration (AMD) patients using confocal scanning laser ophthalmoscopy and spectral-domain optical coherence tomography (SD-OCT). Methods: A total of 18 patients with avascular serous PED underwent assessment of best-corrected visual acuity, infrared (IR) reflectance, fundus autofluorescence (FAF), fluorescein angiography (FA), indocyanine green angiography (ICGA), and SD-OCT evaluation at baseline and at last follow-up visit. The imaging of avascular PED was compared with vascularized PED. Results: A total of 23 eyes with 15.5 ± 6.4 months' follow-up were included. Imaging revealed 3 features associated with avascular serous PED. A reticular pattern, highly reflective (IR), and hyperautofluorescent matching with a reticular area of decreased fluorescence (FA and ICGA) was constantly observed (23/23 eyes). This reticular pattern correlated on SD-OCT with dense hypereflective deposits beneath and within the sensory retina. This reticular pattern was observed in only 2/19 eyes with vascular serous PED (p<0.05). A sharp border of increased IR reflectance, matching with a halo of reduced fluorescence on both FAF and late FA frames, was observed in 23/23 eyes. This sharp border appeared as a sharp hypofluorescent border on late ICGA frames, and as an abrupt elevation of the retinal pigment epithelium on SD-OCT. Hyporeflective fluid beneath the foveal depression was observed in 17/23 (74%) eyes. Only 1/23 eyes developed choroidal neovascularization during the follow-up. Conclusions: Integrated imaging shows peculiar features of avascular PED and possibly contributes to distinguishing this clinical identity from neovascular AMD.